Cameroon Virescens Oil Palm (Elaeis guineensis) from IOPRI’s Germplasm - Heri Adriwan Siregar; Yurna Yenni; Retno Diah Setiowati; Nanang Supena; Edy Suprianto; Abdul Razak Purba (AGRIVITA, Journal of Agricultural Science, 2020)
In the assumption of oil palm breeders, virescens oil palm type has no real economic value. Therefore, the nigrescens is more considered. However, the virescens gives a visual cue that fruits are ripe without waiting to detach. In 2010, Indonesian Oil Palm Research Institute (IOPRI) successfully planted an open-pollinated population of Cameroon oil palm. The population was characterized for virescens type frequency, as well as the bunch components, quantity and quality of crude palm oil. The virescens frequency per accession was sufficiently wide, ranging from 3.33-65.71%, and was affected by the parent type, nigrescens or virescens. Most of the virescens’s fruit form is observed to be of dura, except one sample, which was observed to be tenera. The mesocarp to fruit (MF) and industrial extraction ratio (IER) percentage are similar to the nigrescens dura, namely 37.7% and 9.5%, respectively. Its oil quality is better than nigrescens, and it has total carotene ranging from 155-1246 ppm. The oleic fatty acid is higher than 50%, and the palmitic is lower than 40%. Due to the ease of determining mature fruits, as well as the higher oil quality, virescens oil palm type is recommended to be introgressed in a breeding program.